Case reportPercutaneous closure of Waterston shunt in an adult after correction of congenital heart disease – a case report - Demkow, Marcin; Biernacka, Elżbieta Katarzyna; Kwaśniak, Dominika; Zaborowska, Emilia; Petryka, Joanna; Stępińska, Janina; Hoffman, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
We present a 30-year-old man with a history of correction of congenital heart disease and two palliative shunts (Blalock-Taussig and Waterston), who was admitted to our hospital for worsening of heart failure. The echocardiogram showed severe pulmonary regurgitation, both ventricles hypokinetic, left ventricular ejection fraction 20%. Magnetic resonance imaging demonstrated Waterston shunt (Qp : Qs = 3 : 1). The patient was symptomatic and intensive intravenous pharmacological treatment was not effective. Percutaneous closure of Waterston shunt was performed. After intervention the patient was stable on oral treatment.